2019
DOI: 10.1002/eqe.3184
|View full text |Cite
|
Sign up to set email alerts
|

Near‐fault acceleration pulses and non‐acceleration pulses: Effects on the inelastic displacement ratio

Abstract: Summary Near‐fault ground motions can impose particularly high seismic demands on the structures due to the pulses that are typically observed in the velocity time‐histories. The velocity pulses can be further categorized into either a distinct acceleration pulse (acc‐pulse) or a succession of high‐frequency, one‐sided acceleration spikes (non‐acc‐pulse). The different characteristics of velocity pulses imply different frequency content of the ground motions, potentially causing different seismic effects on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Ratios. e inelastic displacement ratios usually have a clear "bump" at the medium period region due to the influence of the predominant velocity pulse [19]. Previous studies have shown that the pulse period is an important parameter influencing the locations of the bump.…”
Section: Effects Of the Pulse Period On The Inelastic Displacementmentioning
confidence: 99%
See 1 more Smart Citation
“…Ratios. e inelastic displacement ratios usually have a clear "bump" at the medium period region due to the influence of the predominant velocity pulse [19]. Previous studies have shown that the pulse period is an important parameter influencing the locations of the bump.…”
Section: Effects Of the Pulse Period On The Inelastic Displacementmentioning
confidence: 99%
“…e pulse period and the pulse intensity are the two key parameters to describe the pulse features. Many studies have analyzed the effects of the pulse period [18][19][20], ground motion parameters [15,17,21], and structural characteristics, such as nonlinear behavior [20,22,23] and soil-structure interaction [24]. However, to the best of our knowledge, there is no study on the impact of pulse intensity.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Yet, amplification of the torsional response is observed when the pulse period is close to the fundamental torsional period of the structure 10 and orientation of the strongest velocity pulse can occur along a direction different from the strike-normal and strike-parallel ones. 11,12 Nowadays, time-frequency domain [11][12][13][14][15] and response spectrum 16,17 methods are available in the literature to detect pulses in ground motions and, more recently, to retain the impulsive effect of the original ground motion on structures. 18 At the same time, pulse indicators are proposed to characterise pulse-like and non-pulse-like near-fault earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…Attention is focused on the pulse-type and non-pulse-type near-fault earthquakes, 11 identifying potential pulses in the acceleration time-histories by means of an automated algorithm. 13…”
Section: Introductionmentioning
confidence: 99%
“…is recognition method greatly improves the efficiency of recognition [19]. For the effect of pulse on the structure, some scholars further divided the velocity pulses into distinct acceleration pulses and nonacceleration pulses according to the impact of earthquake on the structure and the content of different frequency components of ground motion [20].…”
Section: Introductionmentioning
confidence: 99%